Risk estimates of mycotoxin mixtures in the diets of our children - Alvito, Paula (2018)
Co-contamination of foodstuffs with multiple mycotoxins is being reported at an increasing high rate (Alvito et al, 2010; Stoev, 2015; Assunção et al, 2015) and this fact constitutes a rising concern due to the hazard of exposure of combined mycotoxins to humans, which could be expected to exert greater toxicity and carcinogenicity than exposure to single mycotoxins (Bouaziz et al., 2008; Grenier & Oswald, 2011). Most studies have focused on the risk assessment of single mycotoxins and there are scarce data concerning the risk associated with human exposure to multiple mycotoxins in foods, especially for those intended for children consumption (Assunção et al, 2016). Children are a vulnerable part of the population due to, in part, their physiology, a restricted diet and a higher consumption relative to their body thus particular attention must be given to the exposure of this population group to co-occurring food contaminants. Children in many parts of the world are routinely exposed to many mycotoxins in the food chain and the three most common are aflatoxins, fumonisins and deoxynivalenol (Etzel, 2006). For the main mycotoxin groups, maximum levels for regulatory purpose already exist for foodstuffs for adults and children consumption. European legislation (Commission Regulation 1881/2006), regulates processed cereal-based foods, infant formulae and baby foods for infants and young children with respect to mycotoxins contents. Children exposure to single mycotoxins with contents below legislated limits is considered safe to protect human health. Although, whether the children is also protected against a combined exposure to mycotoxins is unknown. MYCOMIX, a recent Portuguese project (https://www.youtube.com/watch?v=CsKaz3mt2J4), assessed for the first time, the risk associated with the simultaneous exposure to 13 mycotoxins in breakfast cereals, processed cereal-based foods and biscuits consumed by children until 3 years old from Lisbon region, Portugal (Assunção et al, 2015; Martins et al, in revision). Results on mycotoxins occurrence showed that 94% of the analysed samples were contaminated with at least one mycotoxin, although at levels below the legislated limits. Co-contamination was observed in 75% of the analysed samples. Estimated aflatoxins exposure suggested a potential adverse health effect for percentiles of intake above or equal to P50, determined through margin of exposure concept (Assunção et al, submitted). Studies on children exposure using mycotoxin biomarkers and attainment of detailed toxicological data, including health consequences associated to exposure to multiple mycotoxins, are needed in order to perform a more accurate risk assessment and to improve the protection of children´s health.